Assessing the Progress of Stock Rebuilding in the Northeast Atlantic Against Levels That Can Produce Maximum Sustainable Yield - Henning Winker; Massimiliano Cardinale; Rishi Sharma; Laurence T. Kell; Iago Mosqueira; Christopher Griffiths (Fish and Fisheries, 2026)
Rebuilding fish stocks to levels above which they produce Maximum Sustainable Yield (MSY) is a management aim for all European commercially exploited stocks. Progress is typically monitored against the fishing mortality that produces MSY in the long term ( F MSY ), however, the corresponding biomass target ( B MSY ) is rarely evaluated nor reported. Here, we analyse a unique database of 73 quantitative ICES stock assessments to provide estimates of B MSY across the Northeast Atlantic and apply a Bayesian state‐space model to estimate joint trajectories of F / F MSY and B / B MSY . Our results confirm that median fishing mortality has substantially decreased from its peak in 1999 to just below F MSY in 2020. Despite this, approximately half of the stocks remain fished above F MSY , with 36% exceeding 1.2 × F MSY . Biomass increased on average from below 0.5 B MSY in 2000 to 0.68 B MSY in 2020, but only 40% of stocks are currently above B MSY and only 35% have an age structure that is comparable with fishing at F MSY . Biomass relative to the ICES trigger point (MSY B trigger ) indicates that more than 70% of stocks are currently within safe biological limits. However, using MSY B trigger as a surrogate for B MSY results in an over‐optimistic classification of stock status, which conflicts with past levels of exploitation and may hinder stock rebuilding and the achievement of MSY objectives. Future projections from individual assessment forecasts predict further increases in B / B MSY under current F levels. However, to achieve B MSY by 2030, a ‘perfect’ implementation of the ICES Advice Rule would be required.